Uncertainty, Capital Investment, and Risk Management - Doshi, Hitesh; Kumar, Praveen; Yerramilli, Vijay (Management science, 2018)
We use forward-looking and exogenous measures of output price uncertainty to examine the effect of price uncertainty on firm-level capital investment, risk management, and debt issuance. The effects of uncertainty vary significantly by firm size. When faced with high price uncertainty, large firms increase their hedging intensity but do not lower capital investment or debt issuance. In contrast, small firms do not adjust their hedging intensity but significantly lower capital expenditure and debt issuance even after controlling for investment demand. Moreover, the negative effect of uncertainty on capital investment is significantly weaker for firms that hedge their output price risk. Our analysis highlights that, in the presence of financial frictions, high price uncertainty has significant dampening effects on capital investment of small firms by exacerbating their financial constraints, and that this negative effect is amplified by firm-level constraints on ability to hedge risk exposures. The Internet appendix is available at https://doi.org/10.1287/mnsc.2017.2815 . This paper was accepted by Amit Seru, finance.